2005
DOI: 10.1249/01.mss.0000177478.14500.7c
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Usage of Intramyocellular Lipids and Glycogen during Exercise

Abstract: During this 3-h exercise, energy supplies from fat and CHO were similar in both genders, and males as well as females reduced their IMCL stores significantly. The larger contribution of IMCL during exercise in males compared with females could either be a result of gender-specific substrate selection, or different long-term training habit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 34 publications
6
56
2
Order By: Relevance
“…In addition, creatine signals did not vary before and for sufficiently long period after exercise in an MR study (65). Similar to the calibration with water, the shape and size of the voxel are the same as for IMCL.…”
Section: Calibration By the Creatine Signalmentioning
confidence: 64%
See 2 more Smart Citations
“…In addition, creatine signals did not vary before and for sufficiently long period after exercise in an MR study (65). Similar to the calibration with water, the shape and size of the voxel are the same as for IMCL.…”
Section: Calibration By the Creatine Signalmentioning
confidence: 64%
“…Besides the direct influences as mentioned above, numerous publications reported a potential influence of other factors upon IMCL levels, such as short-term training (61), oxygenation (62,63), age (64), gender (65)(66)(67), obesity (68), training status (61), muscle group (51,69) or pennation angle (70). A summary of all physiological and pathophysiological consequences of the factors mentioned above would go beyond the target of this text; however, it is important to be aware of all potential factors if a study is not to be influenced by uncontrolled, concomitant factors.…”
Section: Various Other Influences Upon Imcl Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Replenishing carbohydrates during exercise maintains or increases the body's carbohydrate oxidation rate [11], maintains the blood glucose level [12], helps reduce the rate of perceived exertion [13], and slows glycogenolysis in the liver [14] and muscles [15], thus delaying the onset of fatigue during exercise [11]. It has also been reported that consuming additional carbohydrates after exercise increases muscle glycogen synthesis and is thus positively correlated with glycogen retention per hour during recovery [16].…”
Section: Introductionmentioning
confidence: 99%
“…Glycogen and unsaturated fatty acid concentrations measured with the ERETIC method were in excellent agreement with internal creatine and external phantom reference methods, showing a difference of 1.85 6 1.21% for glycogen and 1.84 6 1.00% for unsaturated fatty acid between ERETIC and creatinebased quantification, whereas the deviations between external reference and creatine-based quantification are 6.95 6 9.52% and 3.19 6 2.60%, respectively. Magn Reson Med 67: [1][2][3][4][5][6][7]2012. V C 2011 Wiley Periodicals, Inc. Key words: 13 C magnetic resonance spectroscopy; glycogen quantification; inductive coupling; electric reference to access in vivo concentrations; unsaturated fatty acid concentration Millimolar (mM) concentrations of metabolites in specific tissues are of fundamental interest to the understanding of metabolism in clinical diagnostics and physiological studies.…”
mentioning
confidence: 99%